Factors Affecting Employee Work Productivity During the Covid-19 Pandemic - Encep Saefullah; Arta Rusidarma Putra; Tabroni Tabroni (Institute of Computer Science (IOCS), 2022)
The variables of this research are Leadership (X1), Compensation (X2), Work Discipline (X3), Work Environment (X4), Work Supervision (X5) and Work Productivity (Y). The purpose of this study was to determine the effect of variables X1, X2, X3, X4 and X5 on variable Y partially and simultaneously during the Covid-19 pandemic. This study uses a statement instrument distributed to 68 employees of PT.